Fotografias esquecidas: um encontro com a memória - Emilião, Milena Faria (2014)
This research aimed to understand which relations arising from the study of memory and photography, from a particular photo. For this, two fronts study was designed: a theoretical, seeking the authors Philippe Dubois, Roland Barthes, Susan Sontag, Ivan Izquierdo and Etienne Samain, framework to understand these relations, and another step is practical that try to understand what, in a photography, determines its place in the memories or in limbo. Two communication formats built the gateway to this universe: visuality, exposed through the old photografy, and verbality, from interviews with the people present in the photograph in question. The study sought to find something new about the relationship between people's memories, from photos that are not stored in albums: the "forgotten photographs" as we started to call them here: joining two ways of communication image and word. The problem is to see what happens when people come in contact with old photos that are not recorded. In this sense, the research aims to not only think of photography as a communication object but as a support for memory and oblivion as you choose what to keep and what to leave